2016
DOI: 10.1007/s00018-016-2360-5
|View full text |Cite|
|
Sign up to set email alerts
|

Phospholipid flippases attenuate LPS-induced TLR4 signaling by mediating endocytic retrieval of Toll-like receptor 4

Abstract: P4-ATPases are lipid flippases that catalyze the transport of phospholipids to create membrane phospholipid asymmetry and to initiate the biogenesis of transport vesicles. Here we show, for the first time, that lipid flippases are essential to dampen the inflammatory response and to mediate the endotoxin-induced endocytic retrieval of Toll-like receptor 4 (TLR4) in human macrophages. Depletion of CDC50A, the β-subunit that is crucial for the activity of multiple P4-ATPases, resulted in endotoxin-induced hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 72 publications
3
35
1
Order By: Relevance
“…Said interaction, seemed to depend on TLR4 since pretreatment of cell cultures with C34 blunted PPIs-induced changes in the activity of these compartments. Endocytic retrieval of TLR4 is mediated by intracellular pathways (i.e., MCP-1 and IL-8) that are activated by phospholipids (PLs) [21]. To elucidate the potential of PPIs to induce changes on PLs content in HB8902 cells, the total PL content in cells cultures challenged to PPIs was quantified ( Figure 3D).…”
Section: Phenotypic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Said interaction, seemed to depend on TLR4 since pretreatment of cell cultures with C34 blunted PPIs-induced changes in the activity of these compartments. Endocytic retrieval of TLR4 is mediated by intracellular pathways (i.e., MCP-1 and IL-8) that are activated by phospholipids (PLs) [21]. To elucidate the potential of PPIs to induce changes on PLs content in HB8902 cells, the total PL content in cells cultures challenged to PPIs was quantified ( Figure 3D).…”
Section: Phenotypic Changesmentioning
confidence: 99%
“…The latter, favored a rapid production of energetic and reducing equivalents as well as increased levels of Krebs cycle intermediates, in concordance with the variations in OCR (pmol min −1 ) ( Figure 3A), supporting an increased non-mitochondrial respiration. The variation of key mediators in glycolysis-P04406, P00558, P18669, P14618, O75874 and P40925-indicate an adaptation towards low utilization of carbohydrates together with the accumulation of tricarboxylic acid cycle intermediates (i.e., citrate, malate) favoring a classical and innate (i.e., TLRs)-induced M1 phenotype [21,26]. Otherwise, macrophage activation through the alternative pathway engaged modest metabolic events.…”
Section: Phenotypic Changesmentioning
confidence: 99%
“…The selected proteins have previously been reported to be associated with immunity and other infectious diseases [24][25][26][27][28][29][30][31][32][33][34][35]. XRCC4 is an important component of non-homologous end-joining [24].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that lipid flippases are essential to mediate the endotoxin-induced endocytosis of Toll-like receptor 4 in human macrophages. Macrophages play a primary role in TB transmission [35]. MTB usually replicates within macrophages and spreads to pulmonary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Site cg08504659 (discovery phase: HR=1.34, P =7.53×10 −6 ; validation phase: HR=1.22, P =1.58×10 −4 ) is located within PTGDR (encoding prostaglandin D2 receptor), which is a mediator of allergic inflammation and is recognized as a drug target of asthma [3]. Another site, cg04740513 (discovery phase: HR=0.97, P =1.23×10 −5 ; validation phase: HR=0.98, P =1.06×10 −4 ), is located within ATP11A (encoding integral membrane ATPase), which is associated with pulmonary disorders related to inflammation and fibrosis [4] and was recently identified as a novel element of the innate immune response and inflammatory response [5]. …”
Section: Dear Editormentioning
confidence: 99%